Implementation of Gratitude Program to Increase Employee Resilience and Loyalty in the Workplace - Saputra, Silvia (CV. Publikasi Indonesia, 2024)
This research aims to examine the effect of the implementation of the gratitude program on employee resilience and loyalty in the workplace. Using a qualitative approach with in-depth interviews and focused group discussions, the study involved 20 employees from various divisions in a company that had implemented a gratude program. The results of the study show that this program increases employee resilience through activities such as gratitude sharing sessions and gratitude journal writing, as well as increasing employee loyalty by strengthening appreciation and attachment to the company. These findings indicate that gratitude programs are effective in creating a positive work environment, improving psychological well-being, and strengthening interpersonal relationships in the workplace. This research contributes to the development of HR management theory and offers practical implications for companies in increasing employee resilience and loyalty.